If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 157 + -4x = 6x + 7 Reorder the terms: 157 + -4x = 7 + 6x Solving 157 + -4x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 157 + -4x + -6x = 7 + 6x + -6x Combine like terms: -4x + -6x = -10x 157 + -10x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 157 + -10x = 7 + 0 157 + -10x = 7 Add '-157' to each side of the equation. 157 + -157 + -10x = 7 + -157 Combine like terms: 157 + -157 = 0 0 + -10x = 7 + -157 -10x = 7 + -157 Combine like terms: 7 + -157 = -150 -10x = -150 Divide each side by '-10'. x = 15 Simplifying x = 15
| 3(2m+3)=-15 | | -7y-7=-3-4y | | n-13=12 | | 1x+21=6 | | -5x+6(-3x-3)=-36-5x | | -8-p=-12-3p | | C^2+15c+36=0 | | -3t+1=t+9-4t | | 6+8x=34+x | | 3x-32=3x+3 | | 5x+40=13x-48 | | 3x-7y=11 | | 7x+7y=0 | | 8x-11=4x+1 | | 1.2h-4.7=5.6h-18.18 | | 2(p+2)=1.8p-2-0.2(p+5) | | 6x+4y=48 | | 85-5x=40x+20 | | 14-10x=32-17x | | -36-10x=10x+24 | | 6(s-4)=3(s+9) | | 2(2x+3)=3(x+10) | | 154-3x=42x+24 | | x^2+9y^2-4x=32 | | 6x-8=6x+8 | | 8-9x=100-37x | | e=[-(20-17.4)+25]-(-17.4+25) | | 3x-4x=2 | | -116-8x=7x+19 | | Y=x^2+8x+12 | | 4z^2-4z-3=0 | | -14=-2+8v+4v |